INCREASED INCIDENCE OF ASTHMA IN HIV-INFECTED CHILDREN TREATED WITH HAART IN THE NIH WOMEN AND INFANTS TRANSMISSION STUDY - Foster, Samuel B. (2008)
BACKGROUND: Immunoreconstitution of HIV-infected (HIV+) patients after treatment with highly antiretroviral therapy (HAART) appears to provoke inflammatory diseases. OBJECTIVE: Determine whether HIV+ children on HAART (HIV+ HAART+) have a higher incidence of asthma than HIV+ children not on HAART (HIV+ HAART−). METHODS: To investigate this possibility, 2,664 children (193 HIV+, 2,471 HIV−) born to HIV+ women were evaluated for the incidence and prevalence of asthma (i.e., asthma medication use), and change of CD4(+) T cell percentage with time. RESULTS: The HIV+ HAART+ children had higher CD4(+) T cell percentages, lower CD8(+) T cell percentages, and lower viral burdens than the HIV+ HAART− children (P≤0.05 to P≤0.01). The cumulative incidence of asthma medication use in HIV+ HAART+ children at 13.5 year rose to 33.5% vs. 11.5% in HIV+ HAART− children (hazard ratio=3.34, P=0.01) and was equal to that in the HIV− children. In children born prior to the HAART era, the prevalence of asthma medication use for HIV+ HAART+ children at 11 years of age was 10.4% vs. 3.8% for HIV+ HAART− children (odds ratio=3.38, P=0.02) and was equal to that of the HIV− children. The rate of change of CD4(+) T cells (percent/year) around the time of first asthma medication for HIV+ HAART+ vs. HIV+ HAART− children was 0.81 vs. −1.43 (P=0.01). CONCLUSION: The increased incidence of asthma in HIV+ HAART+ children may be driven by immunoreconstitution of CD4(+) T cells. CLINICAL IMPLICATIONS: This HIV model of pediatric asthma may yield clues to help explain the epidemic of asthma in the general pediatric population.